2017
DOI: 10.3389/fpls.2017.02021
|View full text |Cite
|
Sign up to set email alerts
|

Transcript Profiling Identifies Gene Cohorts Controlled by Each Signal Regulating Trans-Differentiation of Epidermal Cells of Vicia faba Cotyledons to a Transfer Cell Phenotype

Abstract: Transfer cells (TCs) support high rates of membrane transport of nutrients conferred by a plasma membrane area amplified by lining a wall labyrinth comprised of an uniform wall layer (UWL) upon which intricate wall ingrowth (WI) papillae are deposited. A signal cascade of auxin, ethylene, extracellular hydrogen peroxide (H2O2) and cytosolic Ca2+ regulates wall labyrinth assembly. To identify gene cohorts regulated by each signal, a RNA- sequencing study was undertaken using Vicia faba cotyledons. When cotyledo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…A transcriptome database of trans -differentiating ETCs and their underlying storage parenchyma cells of cultured V. faba cotyledons, annotated in Mapman Mercator and KEGG (Zhang et al , 2017 b ), was used to investigate expression profiles of transcripts with RPKMs (reads per kilobase of transcript per million mapped reads) >1 and encoding full-length sequences of proteins participating in apo H 2 O 2 biosynthesis and catabolism. Differentially expressed genes (DEGs) were defined as those exhibiting log 2 fold change (FC) values >1 between two consecutive time points with a false discovery rate- (FDR) corrected P -value of <0.05 calculated using LimmaR (Ritchie et al , 2015).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A transcriptome database of trans -differentiating ETCs and their underlying storage parenchyma cells of cultured V. faba cotyledons, annotated in Mapman Mercator and KEGG (Zhang et al , 2017 b ), was used to investigate expression profiles of transcripts with RPKMs (reads per kilobase of transcript per million mapped reads) >1 and encoding full-length sequences of proteins participating in apo H 2 O 2 biosynthesis and catabolism. Differentially expressed genes (DEGs) were defined as those exhibiting log 2 fold change (FC) values >1 between two consecutive time points with a false discovery rate- (FDR) corrected P -value of <0.05 calculated using LimmaR (Ritchie et al , 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Plumes of elevated [Ca 2+ ] cyt determine foci at which WI papillae are deposited through remodelling an actin-dependent delivery of vesicles carrying cargoes of wall building materials (Zhang et al ., 2015 a , 2017 a ). Strikingly, a recent ETC-specific transcriptome study in which each signal was silenced by selective pharmacological blockade found that the apo ROS signal exerted the greatest regulatory influence over gene expression (Zhang et al , 2017 b ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Induced adaxial ETCs of cultured cotyledons of faba bean have provided considerable insights into mechanisms regulating reticulate WL development (e.g. Andriunas et al ., 2013; Zhang et al ., 2015a–d, 2017a,b, 2019; Xia et al ., 2017, 2020). Upon cotyledon transfer to culture, their adaxial epidermal cells, which do not form ETCs in vivo , rapidly (within 12 h), semisynchronously, trans ‐differentiate to a TC phenotype (Fig.…”
Section: Critique Of Experimental Systems Used To Study Transfer Cellmentioning
confidence: 99%